Determinación de la composición nutricional del fruto de pechiche (Vitex gigantea Kunth) - Solis Coello, Marcos Darwin (2017)
In the present work the content of the macronutrients, micronutris and the caloric value in the fruit pechicche were determine by the AOAC methods and mathemsticsl.......................................................